The Mechanism and Dynamic Regulation of Epithelial to Mesenchymal Transition in Ovarian Cancer - Pande Kadek Aditya Prayudi; I Gde Sastra Winata; I Nyoman Bayu Mahendra; I Nyoman Gede Budiana; Kade Yudi Saspriyana; Ketut Suwiyoga (Clinical and Experimental Obstetrics & Gynecology)
Objective: To understand the basic mechanism and dynamic regulation that underlies the epithelial-to-mesenchymal transition (EMT) in ovarian cancer (OC) cells. Mechanism: A literature review using evidences from several data bases (i.e., PubMed, EMBASE, Web of Science, Medline, Cochrane, Science Direct, and Google Scholar) were conducted to describe the basic mechanism and dynamic regulation of EMT in OC cells. Finding in Brief: EMT is a complex epigenetic reprogramming orchestrated by specific transcription factors (TFs) and multiple upstream activators and regulators, such as transforming growth factor-β (TGF-β), Wnt, Hedgehog, and Hippo signaling pathways. The net result of this cellular reprogramming is the acquisition of mesenchymal phenotypes with increased invasive and metastatic potential, stemness properties and chemoresistance. Recent studies have demonstrated that EMT activation is the result of dynamic and reciprocal interplay between OC cells and their tumor microenvironment (TME). Cellular or non-cellular component of TME, external factors related to TME such as hypoxia, oxidative stress, mechanical forces, as well as exposure to chemotherapy, all play significant role to EMT induction. Current understanding behind the mechanism of EMT induction in cancer cells have proposed the idea that EMT is not merely a binary process involving a complete conversion from epithelial to mesenchymal state, but rather a dynamic process that encompasses a range of hybrid states, a phenotype that has been referred to as “partial EMT”. Cells with partial EMT have been known to be more apoptosis-resistant and have more tumor-initiating potential as compared to those with complete EMT. Conclusions: Understanding the complex regulatory network that underlies EMT in OC cells is crucial in order to gain insight in developing novel and effective treatment strategies for OC.